Hydrothermal synthesis and characterization of visible light-driven I-doped Bi 2 MoO 6 photocatalyst - Phattranit Dumrongrojthanath (2019)
© 2018, Iranian Chemical Society. 0–3% I-doped Bi 2 MoO 6 samples as visible light-driven-photocatalysts were successfully synthesized by a hydrothermal method. Structure, morphology, composition and optical properties of as-synthesized samples were investigated by X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy, BET surface area analysis, X-ray photoelectron spectroscopy, UV–visible absorption and photoluminescence spectroscopy. The photocatalytic activities of Bi 2 MoO 6 and I-doped Bi 2 MoO 6 samples were investigated through degradation of rhodamine B as a pollutant model induced by visible radiation. The experimental results show that Bi 2 MoO 6 exhibits enhanced photocatalytic activity by doping with iodine. In addition, the mechanism for photocatalytic degradation of organic molecules by I-doped Bi 2 MoO 6 was discussed.